SPECT- and PET-Based Patient-Tailored Treatment in Neuroendocrine Tumors: A Comprehensive Multidisciplinary Team Approach. (May 2015) - Werner, R.A.; Bluemel, Christina; Lassmann, M.; Kudlich, T.; Higuchi, T.; Lopci, Egesta; Allen-Auerbach, M.; Colletti, Patrick M.; Rubello, Domenico; Zatelli, M.C.; Herrmann, Ken
Abstract : Abstract: The overexpression of somatostatin receptors on the tumor cell surface of neuroendocrine tumors (NETs) detected by multimodal functional imaging modalities such as SPECT and PET tracers constitutes a therapeutic option using targeting radiolabeled compounds. We will introduce the theranostic concept in general, explain in more detail its development in NETs, and discuss available SPECT and PET tracers regarding their potential for diagnostic imaging, visualization of target expression, and treatment tailoring. Moreover, we will discuss the currently available peptide receptor radionuclide therapy principles and compare them to previously published studies. Finally, we will discuss which new concepts will most likely influence the theranostic treatment approach in NETs in the future.